Pelatihan Penguatan Profil Pelajar Pancasila: Bergotong Royong dengan Tema Team Building Murid-Murid SMP Maitreyawira Deli Serdang - Sutarno, Sutarno; Anggraini, Dewi; Ciamas, Elserra Siemin (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Educational transformation through the Kurikulum Merdeka demands the strengthening of student character, particularly in the "Gotong Royong" (mutual cooperation) dimension of the Pancasila Student Profile. This community service activity aims to enhance the awareness and collaboration skills of SMP Maitreyawira Deli Serdang students through team-building training based on the "Formula One" simulation. The participants included 120 ninth-grade students from diverse ethnic backgrounds. The implementation method involved providing material on "The Big Five" personality theory, self-assessment, and a Lego assembly simulation under strict time pressure. Data were collected through participatory observation and field notes, then analyzed qualitatively. The results indicated that although students theoretically understood their personality profiles, the implementation of teamwork under pressure still faced significant obstacles. Most groups failed to complete tasks on time due to communication barriers and low trust among members who were not previously acquainted. However, certain groups consistently excelled, driven by emotional proximity and effective situational leadership. The conclusion of this service is that the awareness of mutual cooperation requires repetitive and sustainable practice. The primary recommendation for the school is to conduct periodic collaborative simulations with rotating group members to train students' social flexibility in facing future challenges.